Promoting Cultural Tourism - Calhoun, Charles (Maine Policy Review, 2000)
Cultural tourism is one of the fastest growing segments of the tourism industry, attracting visitors who tend to stay longer, spend more, and travel in the off-season. Yet, as Calhoun observes, the idea that Maine offers culture as well as scenery is still not part of the state’s self-image. Calhoun urges regions to think creatively and comprehensively about their cultural resources. Among other things, Calhoun encourages the development of regional cultural trails where tourists are linked from one destination to the next. He argues that in the southern- and mid-coast regions, such an approach could help to alleviate coastal pressure by directing tourists inland. Calhoun concludes with eight recommendations for Washington County, Maine, where tourism is vital to a more prosperous economic future.